The Effect of Organizational Culture, Personality, and Job Satisfaction Toward Employees Performance In Directorate General Of Industrial Resilience And International Access Development (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of this study was to determine the effect of organizational culture, personality, and job satisfaction towards employee’s performance in the Directorate General of Industrial Resilience and International Access Development. This research tried to answer problems about the performance issues with increasing evidence of a decreased of organizational performance backed by its employees’ performance assessment data. The research was conducted on performance involving 79 employees that had been selected from a target Populations of 99 employees by using the quantitative approach with path analysis methods. The research of hypothesis testing shows that: (1) organizational culture had a direct positive effect on performance; (2) personality had a direct positive effect on performance; (3) job satisfaction had a direct positive effect on performance; (4) organizational culture had a direct positive effect on job satisfaction: (5) personality had a direct positive effect on job satisfaction: Therefore, to improve the employee performance in the Directorate General of Industrial Resilience and International Access Development an increase is organizational culture, personality and job satisfaction need to be done. Keywords: Performance, Organizational Culture, Personality, Job Satisfaction.